2009
DOI: 10.1111/j.1470-6431.2009.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of 3‐D visualization technology: the potential impact on interior design and its consumers

Abstract: Three-dimensional visualization has developed and improved significantly over the last several decades and resulted in consumers' having multidimensional, multi-sensory experiences with a wide range of products and services. It has affected the built environment and its related businesses. Designers create 3-D images and walk-through animations to communicate with their clients more clearly, starting from the early stage of the design process. The interior-design-related material manufacturers and retailers ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The independent variables highly visited in this theme include interactivity (Chan et al, 2022; Chang et al, 2014; Goh & Ping, 2014; Kahn, 2017; Kim et al, 2021; Li et al, 2021; Ning Shen & Khalifa, 2012; Petit et al, 2022; Qin et al, 2021; Ramani & Kumar, 2008; Suh & Lee, 2005; Willems et al, 2019; Yim et al, 2017), vividness (Choudhary et al, 2021; Lee, 2009; Ning Shen & Khalifa, 2012; Suh & Lee, 2005; Yang & Xiong, 2019; Zhang et al, 2018), immersion (Kowalczuk et al, 2021; Petit et al, 2022; Vishwakarma et al, 2020; Yim et al, 2017), enjoyment (Chan et al, 2022; Chung et al, 2018; Lee, Zhao, & Lee, 2019; Manis & Choi, 2019; Nascimento et al, 2018; Pillai et al, 2020; Roy et al, 2017; Yang & Xiong, 2019; Yim et al, 2017; Yim & Park, 2019), innovativeness (Chung et al, 2015; Flavián et al, 2022; Ing et al, 2020; Lee & Shin, 2018; Pillai et al, 2020), ease of use (Chung et al, 2015; Chung et al, 2018; Flavián et al, 2022; Lee, Kim, & Choi, 2019; Pillai et al, 2020), perceived usefulness (Chung et al, 2018; Flavián et al, 2022; Kowalczuk et al, 2021; Lee, Kim, & Choi, 2019; Nascimento et al, 2018; Pillai et al, 2020; Vishwakarma et al, 2020; Yim & Park, 2019), perceived security (Chan et al, 2022; Flavián et al, 2022; Lim et al,…”
Section: Research Themes In Consumers' Responses Toward Smart Technologymentioning
confidence: 99%
“…The independent variables highly visited in this theme include interactivity (Chan et al, 2022; Chang et al, 2014; Goh & Ping, 2014; Kahn, 2017; Kim et al, 2021; Li et al, 2021; Ning Shen & Khalifa, 2012; Petit et al, 2022; Qin et al, 2021; Ramani & Kumar, 2008; Suh & Lee, 2005; Willems et al, 2019; Yim et al, 2017), vividness (Choudhary et al, 2021; Lee, 2009; Ning Shen & Khalifa, 2012; Suh & Lee, 2005; Yang & Xiong, 2019; Zhang et al, 2018), immersion (Kowalczuk et al, 2021; Petit et al, 2022; Vishwakarma et al, 2020; Yim et al, 2017), enjoyment (Chan et al, 2022; Chung et al, 2018; Lee, Zhao, & Lee, 2019; Manis & Choi, 2019; Nascimento et al, 2018; Pillai et al, 2020; Roy et al, 2017; Yang & Xiong, 2019; Yim et al, 2017; Yim & Park, 2019), innovativeness (Chung et al, 2015; Flavián et al, 2022; Ing et al, 2020; Lee & Shin, 2018; Pillai et al, 2020), ease of use (Chung et al, 2015; Chung et al, 2018; Flavián et al, 2022; Lee, Kim, & Choi, 2019; Pillai et al, 2020), perceived usefulness (Chung et al, 2018; Flavián et al, 2022; Kowalczuk et al, 2021; Lee, Kim, & Choi, 2019; Nascimento et al, 2018; Pillai et al, 2020; Vishwakarma et al, 2020; Yim & Park, 2019), perceived security (Chan et al, 2022; Flavián et al, 2022; Lim et al,…”
Section: Research Themes In Consumers' Responses Toward Smart Technologymentioning
confidence: 99%
“…It is a simulated environment where users can interact with virtual objects (i.e. pet products in this study) through a mediating technology (Lee, 2009). Based on the degree of immersion into the virtual environment, VR systems can be divided into three categories: fully immersive systems, non-immersive desktop systems and semi-immersive projection systems (Mujber et al , 2004).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A non-immersive VR simulates the virtual environment on a computer screen for users to experience: users manipulate and interact with the environment using input devices such as mice, keyboards, joysticks and trackballs (Lee, 2009; Mujber et al , 2004). Non-immersive VR applications are less expensive and more commonly used (Lee, 2009; Mujber et al , 2004) and can induce a certain degree of immersion for users, although the degree of immersion is lower than semi-immersive and fully immersive systems (Mujber et al , 2004). Past studies have examined non-immersive VR systems and indicated that virtual product experiences work better than traditional offline presentation modes or the base interface condition (i.e.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…the look and feel of the premisesas well as the processes and encounters between people. In PASSME [10] we focused on enhancing passengers experience at airports, through optimizing interiors, luggage flow and offering real-time personalized information. In the remaining sections of the paper, we are discussing the design process adopted within our present research and highlight key findings.…”
Section: Passmementioning
confidence: 99%